KAJIAN PENGARUH ADMIXTURE PADA PAPAN SEMEN BERSERAT BERBUSA RINGAN - Pratikto Pratikto; Anni Susilowati; Eko Wiyono (Politeknik Negeri Semarang, 2022)
Foam mortar can be used as an alternative to cement board mixtures in ceiling or ceiling construction. The purpose of this study was to obtain the physical and mechanical properties of lightweight foamed cement board, to analyze the effect of admixture on bending strength, and to determine the optimum admixture for lightweight foamed cement board. The study used an experimental method by molding cement board test objects. The independent variable for the composition of the mixture with a ratio of 1 Cement: 1.2 Sand: 0.47 w/c ratio, with a mortar ratio of 0.45: 0.55; 31% glass fiber and 1:30 foam agent as well as 6 different admixture variations, namely 0; 0.2; 0.4; 0.6; 0.8 and 1.0%. The dependent variables are density, specific gravity, strength of nailed, and bending strength. The results showed that the higher the admixture content, thee workability. Density and specific gravity are decreasing. Meanwhile, the strength of the cement board is nailed, it does not break, there are no surface cracks, and the nails are easy to pull out. Bending strength was increasing and the optimum at 0.8% admixture variation was 60.44 kg/cm2. For the long term, the composition of this foam mortar mixture can be used as a ceiling